KONDISI DAN PERENCANAAN PEMBANGUNAN KEPENDUDUKAN, SOSIAL, SERTA EKONOMI PADA ERA OTONOMI DAERAH - Marhaeni, A.A.I.N. (PIRAMIDA; Vol. 1, No. 1 April 2005)
Development of population, social, and economic have been implemented in Indonesia, and also Bali Province. However, the achievement is varies among provinces, and among regencies in Indonesia. By using some publication data of Central Bureau of Statistics, tendency of fertility, mortality, educational, income, and Human Development Index in Bali province and each regencies will be analysed. Condition and development of those variables will determine policy applied in the future. From descriptive analysis, some conclusion can be drawn. First, there is a significant decline of fertility in Bali in the period of 1970-2000, but tend to incline in 2002-2003. Second, mortality condition (Infant Mortality Rate) in Bali Province has also declined until the last data (2004) and lower than national data. Third, educational level of Bali population has continually incline, but vary among regencies. Fourth, income condition of Bali Province tend to be better than income of population of provinces in Java, but it is vary among regencies in Bali. Fifth, Population Development Index is relatively higher than provinces in Indonesia, though vary among regencies. As development given to the local government, there must be a commitment of all leaders for continuing policy of fertility, and mortality decline through supporting activities. Besides that those activities for consolidate fund for un-wealthy population in health and family planning service. Additionally, as there is a relatively great gap of development outcome among regencies in Bali which is reflected by the imbalance of Human Development Index among regencies in Bali, so the commitment of government of Bali Province for balancing development outcome among regencies will become a crucial to be done.
Keywords: fertility, mortality, education, income, Human Population Index, and regional autonomy.